Harvesting of botryococcus sp. biomass from greywater by natural coagulants - Hauwa, Atiku; Radin Mohamed, Radin Maya Saphira; Abduh Algheethi, Adel Ali Saeed; Wurochekke, A. A.; Amir, H. K. (Springer, 2017)
Harvesting of Botryococcus sp. from greywater by Moringa oleifera and Strychnos potatorum seed flours was optimized by response surface methodology. Three factors including dosage (10–60 mg L−1), settling time (30– 120 min), and pH (6–9) were investigated. Optimal operating parameters were obtained with dosage of 35 mg L−1, pH of 7.5, and settling time of 75 min, which demonstrated predicted and experimental recovery of 86.80 and 85.60% for M. oleifera, and 41.33 and 38.30% for S. potatorum, with R2 coefficient of 0.947 and 0.953, respectively. The interaction between the factors was significant (p < 0.05) at the optimal operating parameters. Scanning electron microscope (SEM) observed that the surface appearance of M. oleifera seed flour was smoother compared to S. potatorum, which reflects the higher potential of M. oleifera seed flour to adhere to microalgae cells. Natural coagulants have the potential as an alternative technique for harvesting microalgae from greywater.